History of search engines: from Archie to Google - Picalho , Antonio Carlos (2025)
Daily, a person with access and technological familiarity performs dozens of online searches. Search engines have become an integral part of the routine of accessing the internet, since through them users reach content and look for the information they need. With a simple interface and use that does not require extensive technical knowledge, search engines offer an uncomplicated user experience; however, this was not always the case. This essay is presented as a historical-documentary study based on scholarly sources and supported by secondary sources and iconographic material. Its objective is to present the history of search engines from the emergence of Archie, still in the pre–World Wide Web era, to Google, already in the internet era. We observe that the 1990s were a period of great importance for the technological evolution of search engines, which shifted from restricted use by people with access to robust computing technologies to widespread use by the general public.